Well Done!

Incorrect

*f*(*x*) =
6x cubed + 5x squared + 10 over 2x squared - 9
6*x*^{3} + 5*x*^{2} + 10
2*x*^{2} – 9

*f*(*x*) =
x over x squared - 1
*x*
*x*^{2} – 1

*f*(*x*) =
(2x - 1)(2x + 1) over 4x squared + 4x + 1
(2*x* – 1)(2*x* + 1)
*x*^{2} + 1

*f*(*x*) =
x sqaured over x squared + 7x + 12
*x*^{2}
*x*^{2} + 7*x* + 12

*f*(*x*) =
x sqaured + 5x + 6 over (2x + 1)(2x - 1)
*x*^{2} + 5*x* + 6
(2*x* + 1)(2*x* – 1)

*f*(*x*) =
x over x squared - 1
(*x* − 1)
(*x*^{2} − 1)

?

?

?

?

?

?

This rational function has no horizontal asymptote.

This rational function has a horizontal asymptote at *y* = 0.

This rational function has a horizontal asymptote at *y* = 4.

This rational function has a vertical asymptote at *x* = -3.

This rational function has a vertical asymptote at *x* =
1 over 2
1
2
.

This rational function has a hole in the graph at *x* = 1.